An exceptional anticyclonic eddy in the South China Sea in 2010. Issue 2 (12th February 2014) - Chu, Xiaoqing; Xue, Huijie; Qi, Yiquan; Chen, Gengxin; Mao, Qingwen; Wang, Dongxiao; Chai, Fei
Abstract The highest sea level near the Xisha Islands in recent 20 years occurred during August 2010. Satellite altimeter data indicated that the extreme event was largely due to an anticyclonic eddy, whose amplitude exceeded 20 cm and size exceeded 400 km on 11 August 2010. Cruise observations showed the eddy raised the center temperature by 7.7°C at 75 m and vertically extended to 500 m. Eddy tracking showed it had a life span of more than 8 months and propagated far from the south of Xisha Islands. Such strong and long‐lasting eddy that moved northward for such a long distance was observed for the first time in the South China Sea (SCS). Observational data from CTD/XBT and the reconstructed three‐dimensional temperature and salinity were used to explore the eddy's features and vertical structure. Our analyses show the 2010 summer monsoon and current in the western boundary of the SCS were largely altered after the 09/10 El Niño event. From May onward, the wind blew northward and strengthened over the northwestern SCS. Such wind drove a strong northward current along the western boundary, which carried the eddy northward by advection from May to July. Energy budget showed, during the eddy northward propagation, the boundary current passed energy to the eddy, which led to the continuing growth of the eddy in both strength and size.